EVOLVE - A Bridge between Probability, Set Oriented Numerics, and Evolutionary Computation III - Schuetze, Oliver; Coello, Carlos A.; Tantar, Alexandru-Adrian; Tantar, Emilia; Bouvry, Pascal; Moral, Pierre Del; Legrand, Pierrick (Studies in Computational Intelligence,, 2014)
This book comprises a selection of extended abstracts and papers presented at the EVOLVE 2012 held in Mexico City, Mexico. The aim of the EVOLVE is to build a bridge between probability, set oriented numerics, and evolutionary computation as to identify new common and challenging research aspects. The conference is also intended to foster a growing interest for robust and efficient methods with a sound theoretical background. EVOLVE aims to unify theory-inspired methods and cutting-edge techniques ensuring performance guarantee factors. By gathering researchers with different backgrounds, a unified view and vocabulary can emerge where the theoretical advancements may echo in different domains. Summarizing, the EVOLVE conference focuses on challenging aspects arising at the passage from theory to new paradigms and aims to provide a unified view while raising questions related to reliability, performance guarantees, and modeling. The extended papers of the EVOLVE 2012 make a contribution to this goal.